Penurunan Persentase Rework di PT X dengan Metode DMAIC - Hervy Monica Aransa; Debora Anne Yang Aysia (Jurnal Titra, 2015)
PT X is a company which is focused on bag and plastic production. The high percentage of rework which is about 25.5% is one of the problems in this company. The purpose of this research is to decrease the rework percentage in PT X Company by using DMAIC method (Define, Measure, Analysis, Improve and Control). There are three types of defects that often happen based on Pareto Diagram, which are not proportional shapes, less of needlework and over-needlework.  Fishbone Diagram is used to find the cause of defects which are human factors, method and machine. There are six ways to decrease the higher percentage of reworks such as, making operator evaluation form, making sewing pattern using chalk, making a layer to measure the shape of product, rechecking the product at the end of production process, making a list of working instructions  and changing the needle regularly. By implementing four ways, it can reduce the number of defects which are 6 % on not proportional form and 2.27% on less of needlework. It also increases the percentage of over-needlework detects which is 1.33%. In general, there is a decreasing percentage of the number of defects which is about 6.9% after implementation. Control steps using quality plan, is made as a standard that aims to describe the production process, its name, material and characteristics quality which including types of defects, acceptance, measurement method, inspection period, inspection method, person in charge, and the actions based on quality characteristic.